A CASE CONTROL STUDY ON CORRELATION BETWEEN GENITOURINARY INFECTION AND PRETERM LABOUR - Patel, Udaykumar M; Jani, Parul S; Kakani, Chunilal R (National Journal of Medical Research, 2015)
Background: Genitourinary infections leading to pre term labour is well known fact since long. However the issue still prevail in developing countries like India. Objectives: This study was conducted to find out the prevalence of genitourinary infections in the preterm delivery and compare it with the full term deliveries. Patients and methods: A case control study was undertaken in a tertiary care centre. The study comprise of 50 cases of pre term delivery between 28-37 weeks of gestation (case group) and 50 full term cases for comparison (control group). All the cases were subjected to microbiological analysis for bacterial (aerobic), fungal and protozoal examination by two high vaginal swabs and urine samples for routine examination, bacteriological examination, culture and antibiotic sensitivity. Statistical analysis was carried out using chi square and student ‘’t’’ test. Results: In the case group (Group A) of 50 cases of PTL the frequency of genital tract infection, urinary tract infection (UTI) and combined genitourinary infection (GUI) was 44%, 30% and 16% respectively as compared to 10%, 6% and 0% in the Group B, suggesting a statistically significant relationship of prevalence of genital as well as urinary tract infection in patients with preterm labour. The most common causative organisms of UTI were, Escherichia coli (14%) and Klebsiella pneumoniae (12%), while Gardnella vaginalis (16%) and Candida albicans (14%) were found to be commonly associated with genital tract infection. The number of low birth weight babies was significantly higher in intervention group than in the normal group. Conclusions: Integration of a simple infection screening programme into routine antenatal care may reduce the incidence of preterm labour and improve perinatal outcome.